2015
DOI: 10.3109/13880209.2015.1017886
|View full text |Cite
|
Sign up to set email alerts
|

In vitroantioxidant and anti-cholinesterase activities ofRhizophora mucronata

Abstract: Context: Rhizophora mucronata Lam. (Rhizophoraceae), commonly known as Asiatic mangrove, has been used traditionally among Asian countries as folk medicine. Objective: This study investigates the cholinesterase inhibitory potential and antioxidant activities of R. mucronata. Materials and method: Rhizophora mucronata leaves were successively extracted using solvents of varying polarity and a dosage of 100-500 mg/ml were used for each assay. Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 50 publications
3
23
1
2
Order By: Relevance
“…R . mucronata has been shown to have highly effective scavenging towards DPPH, hydroxyl, nitric oxide radicals, and hydrogen peroxide radicals [ 44 , 45 ]. To efficiently utilize the mangrove fungal sources available from a single fungal strain, we attempted to explore the antioxidants of isolated fungi by changing the cultivation media.…”
Section: Discussionmentioning
confidence: 99%
“…R . mucronata has been shown to have highly effective scavenging towards DPPH, hydroxyl, nitric oxide radicals, and hydrogen peroxide radicals [ 44 , 45 ]. To efficiently utilize the mangrove fungal sources available from a single fungal strain, we attempted to explore the antioxidants of isolated fungi by changing the cultivation media.…”
Section: Discussionmentioning
confidence: 99%
“…Different parts of R . mucronata such as the bark and leaves have been used traditionally as astringent and antiseptic, and have been shown to possess activities against bacteria, ulcers, and inflammation (Kokpol et al, 1990 ; Suganthy and Pandima Devi, 2016 ). Furthermore, pharmacological studies have shown that the leaf exhibits antiviral, anti-inflammatory, and anti-diabetic activities (Gaffar et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…A figura 1 representa estudos destacando as atividades biológicas de cada gênero; Avicennia, Conocarpus, Laguncularia e Rhizophora, encontrados no manguezal brasileiro. ABDEL-HAMEED; BAZAID, 2013) (9) ,(ODA, 2017) (10) , (RAZA et al, 2016) (11) ; Atividades biológicas Rhizophora (KUSUMA; KUMAR; BOOPALAN, 2011) (12) , (MELCHOR et al, 2001;FERREIRA et al, 2011;MUSTHAFA et al, 2013) (13) , (SUGANTHY;PANDIMA DEVI, 2016;BERENGUER et al, 2006) (14) , (RAMALINGAM; RAJARAM, 2018) (15) , (CHAKRABORTY; RAOLA, 2017) (16) .…”
Section: Atividades Biológicasunclassified